RANCANG BANGUN ABSENSI MAHASISWA MENGGUNAKAN RFID DENGAN KOMUNIKASI TERPUSAT - Fatoni, Mochammad; Harianto, Harianto; Wibowo, Madha Christian (Journal JCONES, 2013)
Attendance is routine before doing activities such as education in scholls and universities. Time recording attendance sheet when entered to start the activity until the end of the activity. At this time attendance system which is still frequently used manually by using the hand as a tool. In this case made attendance system automatically uses RFID tags as identification cards and RFID reader as the reader of the card. The RFID reader is connected to the microcontroller so that tag can be prossed into a data serial number of students (NIM). The microcontroller used is ATMEGA 1284 P-PU because have 2 serial pieces. This system uses 2 serial contained in the RFID Stater Kit module and WIZ110SR module. Communication of RFID Stater Kit module with microcontroller using a serial after the data is forwarded to the server PC so that the serial communication trough WIZ110SR module. Data from the microcontroller then sent to the server PC to be compared with a database that has been created. This data contains the serial number of students (NIM) and information delays. After the data is compared then the data will be returned to the microcontroller is then displayed on the LCD.